2002
DOI: 10.1614/0890-037x(2002)016[0645:grtpac]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Grass Response to Picloram and Clopyralid Applied Before Seeding1

Abstract: Reduction of weed competition using herbicides is critical to the successful revegetation of weed-infested rangeland. However, little is known about the influence of persistent broadleaf herbicides on the establishment of many desired grasses. The objective of this study was to determine the influence of various rates and times of application of picloram and clopyralid before seeding on two native and two nonnative grasses important to western United States rangeland. The study was conducted in 1997 and 1998 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Picloram (4-amino-3,5,6-trichloro-2-pyridinecarboxylic acid) is a systemic chlorinated herbicide, known as a synthetic auxin. This herbicide is widely used in many countries because of the high efficiency in the control of broadleaf weed and woody plants in pasture, wheat, rice, barley, sugarcane, and other crop fields (Sheley et al, 2002;Nelson and Lym, 2003;Dos Santos and Masini, 2007). As a selective herbicide, many researchers have studied its mechanisms of action on plants (Ortega and Pearson, 2011;Smitha and Nair, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Picloram (4-amino-3,5,6-trichloro-2-pyridinecarboxylic acid) is a systemic chlorinated herbicide, known as a synthetic auxin. This herbicide is widely used in many countries because of the high efficiency in the control of broadleaf weed and woody plants in pasture, wheat, rice, barley, sugarcane, and other crop fields (Sheley et al, 2002;Nelson and Lym, 2003;Dos Santos and Masini, 2007). As a selective herbicide, many researchers have studied its mechanisms of action on plants (Ortega and Pearson, 2011;Smitha and Nair, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the greenhouse all of these species had significantly lower germination in treated compared to control pots, even when seeded into soil that had been treated nearly 1 year before seeding. Results of previous studies of the short‐term effects of herbicides on germination in field settings have been variable: some investigators have found that herbicide treatments did not significantly impact the germination of subsequent seed additions (Sheley et al ; Douglass et al ), while others reported negative effects (Lym & Messersmith ; Ortega & Pearson ; Endress et al ). The difference in results between our greenhouse and field environments, coupled with variable findings from other field studies, suggests that results from greenhouse experiments may represent a maximum potential impact for aminopyralid and picloram treatments at the germination stage, while field results may represent realized and more variable effects of those herbicides for particular field sites.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the only other study that addressed timing of herbicide treatments and seeding of native species in a natural area also found that timing was important for seedling establishment. Sheley et al (), in a 44‐day study of effects of herbicides on graminoids, reported that delaying seeding by 24 or 44 days after herbicide application improved the vigor of several desirable species by 40% in comparison to seeding immediately after application. The positive effect of seeding delay on seed performance of some of the species found in our study adds to a small but growing body of evidence that suggests that timing of integrated management strategies may be critical for successful establishment of species seeded for restoration in invaded areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction and establishment of competitive native plants is critical for the sustainable management of weed infestations and the rehabilitation of desirable ecosystems (Jacobs et al 1999). Seeding perennial grasses following herbicide application can increase establishment and provide sustained weed control through grass competition (Bornman et al 1991;Sheley et al 2002;Barnes 2004;.…”
Section: Introductionmentioning
confidence: 99%